On the prenylation of some indolic and imidazolic bases by oxirane auxiliaries under thermal and microwave conditions. Issue 5 (2007) - Jankowski Jankowski, Christopher K. Christopher K.; Dako Dako, Etienne Etienne; Laouz Laouz, Antoun Bou Antoun Bou; Delaforge Delaforge, Marcel Marcel; Paré Paré, Jocelyn R. J. Jocelyn R. J.; Belanger Belanger, Jacqueline M. R. Jacqueline M. R.
Abstract : The analogue of isoprene, 2-methyl-2-vinyloxirane, a versatile isoprene auxiliary, was reacted with some indolic and imidazolic bases, to add one or more isoprene unit(s), to these compounds. This prenylation was realised by using thermal and microwave assisted pathways, via the nucleophilic opening of the epoxide ring. The biological importance of the prenylated derivatives resides in their potential application as drugs. The aminoacids and small protein biomarkers are obtained from simple epoxide opening reactions. All new compounds were characterised by high resolution NMR, mass spectroscopy, GC-MS and LC-MS as well.